Cases of Presumed Damage in Contractual Liability - Oudah Jaddou , Researcher. Diaa; Abdul Qader Marouf , Prof. Dr. Hussein (Basra studies journal, 2023)
In order to develop a comprehensive or general theory of presumed damage applicable to real-life scenarios, especially considering the concept or theory of presumed fault, a study and investigation of the applications of presumed damage that reinforce its existence is necessary. This involves examining cases in which the legislator explicitly stipulates the presumption of damage in Iraqi law and the laws relevant to the research. After outlining the idea of this study in its theoretical framework, it is crucial to enhance it with practical applications. Any legal theory gains significant importance only when it finds practical applications in the legal field. Presumed damage has numerous practical cases and applications, giving this topic great importance and a distinctive position. These cases reveal that the legislator, to varying degrees, has exempted the affected party from proving the damage suffered. In some cases, the legislator presumes damage conclusively, making it non-disputable. In other instances, the presumption of damage is subject to rebuttal.